Proposed Marketing Strategy Using the 7P Marketing Mix to Strengthen Professionalism Based Brand Identity and Optimize Revenue: A Case Study of Klinik Tumbuh Kembang Anak Lalita - Sekar Anandarri, Nindya; Perdhana Dalimunthe, Gallang (International Journal of Science and Environment (IJSE), 2025)
This study examines the alignment between the professionalism value upheld by Klinik Tumbuh Kembang Anak Lalita and the service experience perceived by customers. Although the clinic positions itself as a professional pediatric developmental care provider, stagnating patient growth from 2021 to 2024 indicates a misalignment between intended brand identity and perceived service quality. The rising number of low-priced competitors further intensifies the need for a consistent value delivery strategy. This research employs a qualitative exploratory case study involving in-depth interviews with internal employees, existing patients, and potential customers (15 participants). Secondary data were obtained from Google Reviews, operational documents, and customer service records. Data were analyzed thematically using the 7P Marketing Mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) as the guiding analytical framework. The findings reveal strong professionalism in clinical domains—particularly in the credibility of developmental pediatricians, psychologists, and therapists. However, significant gaps were identified in four non-clinical elements: Product, People, Process, and Physical Evidence. These include the absence of preventive and continuity care services, inconsistent communication quality, inefficient manual booking processes, and non-standardized physical facilities. Minor gaps were found in Price, Promotion, and Place, particularly regarding loyalty fairness, SEO performance, and access experience. The study concludes that the clinic’s clinical excellence has not been fully supported by operational and experiential consistency, resulting in weakened brand identity alignment. Strategic improvements in preventive service offerings, digitalized processes, service excellence training, and standardized physical environments are recommended to reinforce professionalism perception and improve revenue performance. This study contributes to service marketing literature by demonstrating the application of 7P-based alignment analysis in pediatric healthcare services.